Prevalence and Associated Factors of Absenteeism Among Male Under Graduates Medical Students at University of Science and Technology, Yemen, Sana'a, 2024 - Alkharraz, Nawaf Mohammed Saleh; Alazie, Abdulbaset Abdulla'allah Ali; Alward, Bashar Musaed Naji; Ardam, Basheer Mohammed Ali; Albadaini, Hamza Hammod Abdullah (My University, 2024)
Background: Absenteeism among medical students is a concerning issue, as it can impact academic performance and future healthcare delivery. Aim: this study aimed to determine the prevalence and associated factors of absenteeism among male medical students at the University of Science and Technology, Sana'a, Yemen.